Rancang Bangun Sistem Informasi Dan Aplikasi Marketplace Pemesanan Jasa Service Barang Elektronik - Destia Sri Narahayu; Anggi Andriyadi (Institut Informatika dan Bisnis Darmajaya, 2022)
Electronic goods become an important aspect in everyday life that is very helpful and makes it easier to complete work. When the electronic goods are damaged, people find it difficult to find a technician or service provider due to several factors such as the difficulty of finding a service place and the lack of information services for a trusted and professional electronic service or technician in their field, and also damaged goods must be brought to a service center making it difficult for the community. Making a marketplace application system for ordering services for electronic goods using the OOAD method with stages divided into two, namely OOA (Object Oriented Analysis) and OOD (Object Oriented Design) and described using UML tools. The purpose of this research is to design a marketplace application for ordering services for electronic goods, so that it can make it easier for people to find and order service providers. The results of the system and application of this service booth are very helpful for the community in finding and ordering electronic goods service services according to the user's wishes and can be done anywhere and anytime as well as helping service providers (service shops) in reaching more customers. Keywords: Electronic Goods, Service Application Stations, Service Services.